2015
DOI: 10.1186/s12871-015-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines for the management of neuropathic pain: a systematic review

Abstract: BackgroundThe management of neuropathic pain (NP) is challenging despite it being the recent focus of extensive research. A number of clinical practice guidelines (CPGs) for the management of NP have been published worldwide over the past 2 decades. This study aimed to assess the quality of these CPGs.MethodsWe performed a systematic review of published CPGs for the management of NP. Three reviewers independently assessed the quality of the CPGs using the Appraisal of Guidelines Research and Evaluation II (AGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 24 publications
1
90
0
9
Order By: Relevance
“…Available guidelines and algorithms do not explicitly give recommendations on scar tissue and iatrogenic lesion [6,[23][24][25][26][27]. However, there is general agreement in the surgical community that an already partially or completely damaged nerve or nerve root causing chronic neuropathic pain cannot be restored with any kind of surgery, and symptomatic pain therapy in a multidisciplinary setting is required [37,38]. For patients with spinal instability, re-operation is the most appropriate option.…”
Section: Comparison With Guidelines and Algorithmsmentioning
confidence: 99%
“…Available guidelines and algorithms do not explicitly give recommendations on scar tissue and iatrogenic lesion [6,[23][24][25][26][27]. However, there is general agreement in the surgical community that an already partially or completely damaged nerve or nerve root causing chronic neuropathic pain cannot be restored with any kind of surgery, and symptomatic pain therapy in a multidisciplinary setting is required [37,38]. For patients with spinal instability, re-operation is the most appropriate option.…”
Section: Comparison With Guidelines and Algorithmsmentioning
confidence: 99%
“…In the present study, applicability (median score; 30%) took an unfavorable score. In two studies of Sabharwal, et al, Xie, et al and Deng, et al, this domain obtained the lowest score amongst all domains of the AGREE II instrument and in other studies; applicability domain took weak score among the 6 domains of AGREE II instrument (11,13,(15)(16)(17)(18). The weak scores in applicability domain place emphasis on the necessity of improving the conceptualization in guideline implementation during the development process.…”
Section: Appraising Cpgs By Using the Agree-ii Instrumentmentioning
confidence: 91%
“…Clarity of presentation is concerned with the language, structure, and framework of the guideline and emphasizes clarity, specificity, and unambiguous recommendations (items 15 -17) (8). The study of Birken, et al and Deng, et al showed that assessed guidelines obtained the highest score in this domain (14,15). Also, in the study of Sabharwal, et al, another domain taking high scores was clarity of presentation (median score, 92%) as appraisers found guidelines providing clear recommendations were easily identifiable (13).…”
Section: Appraising Cpgs By Using the Agree-ii Instrumentmentioning
confidence: 99%
“…Management of chronic pain and FBSS is best tackled with a BPS approach necessitating a multidisciplinary collaboration [6]. The NP component was treated with pregabalin [65]. Once the BPS formulation was discussed with the referring GP, conservative treatment was initially attempted [66].…”
Section: Conservative Multidisciplinary Treatmentmentioning
confidence: 99%